Common schools and teachers' seminaries - Stowe, C. E. (Marsh, Capen, Lyon, and Webb, 1839)
Report on elementary public instruction in Europe, made to the General Assembly of Ohio, Dec. 1837.--Normal schools and teacher's seminaries, originally published in the American Biblical Repository for July, 1839.